PLANETARY ORBITS IN AxISYMMETRIC VACUUM GRAVITATIONAL FIELDS (Biological Sciences - PJSIR, 2003)
An exact axisymmetric asymptotically flat field , is deterrnined by Einstein equations, possessing a quadrupole  moment  due to a static mass, may be treated as a perturbation on Schwarlschild  field . Exploiting this, planetary  equations under  the influence of the mentioned gravitational field has been  worked  out. The results exhibit  features that  shed  new light  on  issues in relativistic  celestial  mechanics  and  models of planetary  motion.